Population preferences and attitudes towards COVID-19 vaccination: a cross-sectional study from Pakistan - Muhammad Junaid Tahir; Muhammad Saqlain; Waleed Tariq; Summaiya Waheed; Steven H. S. Tan; Sarim Irhas Nasir; Irfan Ullah; Ali Ahmed (BMC, 2021)
Abstract Background While vaccine development is itself a challenge; ensuring optimal vaccine uptake at population level can present an even more significant challenge. Therefore, this study aimed to assess the Pakistani population's attitude and preferences towards the Coronavirus disease 2019 (COVID-19) vaccine. Method A cross-sectional study was carried out through an online self-administered questionnaire from 27 September 2020 to 11 October 2020. A total of 883 people responded to the survey. The questionnaire included the participants' socio-demographic variables, attitudes, beliefs towards the COVID-19 vaccine and acceptance and rejection of vaccination, and reasons for them. Logistic regression analysis was used to analyze the predictors for vaccine acceptance and willingness to pay for the vaccine. Results A majority (70.8%) of respondents will accept the COVID-19vaccine if available, and 66.8% showed a positive attitude towards vaccination. Monthly family income, education level, self-diagnosis of COVID-19 or a friend, family member, or colleague are significant factors influencing the acceptance of COVID-19 vaccination. The dogma of being naturally immune to COVID-19 was a key reason for the refusal of the vaccine. Less than half (48%) of those who refuse will vaccinate themselves if government officials have made it compulsory. A third (33.9%) of participants were willing to pay up to (7 USD) 1000 Pkr (Pakistani Rupees) for the vaccine. Conclusion The population's positive attitude should be improved by increasing awareness and eradicating false myths about vaccines through large-scale campaigns.